2021
DOI: 10.3390/plants10020372
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of Relations between Pressure Changes along Xylem Vessels and Propagation of Variation Potential in Higher Plants

Abstract: Variation potential (VP) is an important long-distance electrical signal in higher plants that is induced by local damages, influences numerous physiological processes, and participates in plant adaptation to stressors. The transmission of increased hydraulic pressure through xylem vessels is the probable mechanism of VP propagation in plants; however, the rates of the pressure transmission and VP propagation can strongly vary. We analyzed this problem on the basis of a simple mathematical model of the pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 74 publications
(196 reference statements)
1
12
0
Order By: Relevance
“…The hydraulic hypothesis is an alternative hypothesis of VP propagation [ 8 , 31 ]. The hypothesis supposes that local damages induce the propagation of waves of an increased pressure through the plant body, activation of mechanosensitive calcium channels, and an increase in the Ca 2+ concentration in the cytoplasm [ 25 , 31 , 74 , 103 , 111 ].…”
Section: Electrical Signals In Plants: Types and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydraulic hypothesis is an alternative hypothesis of VP propagation [ 8 , 31 ]. The hypothesis supposes that local damages induce the propagation of waves of an increased pressure through the plant body, activation of mechanosensitive calcium channels, and an increase in the Ca 2+ concentration in the cytoplasm [ 25 , 31 , 74 , 103 , 111 ].…”
Section: Electrical Signals In Plants: Types and Mechanismsmentioning
confidence: 99%
“…Our earlier theoretical analysis [ 99 ] showed that the results can be explained by the complex mechanism of VP propagation (e.g., combination of ROS waves with the turbulent diffusion of H 2 O 2 ). Induction of VP on the basis of the combination of ROS waves and hydraulic signals [ 8 , 31 , 34 , 35 , 103 , 111 ] is also possible.…”
Section: Electrical Signals In Plants: Types and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…H + -ATP-ases play an important role in the forming of plant electrical responses, which are local or propagating changes in electrical potential in the plasma membrane and induced by actions of stressors [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. It should be noted that there are several types of electrical responses in higher plants including (i) local electrical responses, which are generated in the irritated zone [ 15 , 16 , 17 ]; (ii) action potentials, which are induced by weak or moderate irritations (e.g., cooling or touch) and actively propagate through the plant body [ 6 , 7 , 8 ]; (iii) variations potentials, which are probably local electrical responses on the propagation of hydraulic and/or chemical signals after action of local damages (e.g., burning, heating, and crush) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; and (iv) system potentials, which are weakly investigated hyperpolarization signals [ 10 , 11 , 12 , 13 , 25 , 26 ]. The electrical responses influence numerous physiological processes (expression of defense genes, synthesis of stress phytohormones, photosynthesis, respiration, phloem mass flow, ATP production, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of VP propagation are still being discussed. The first hypothesis [ 13 , 14 , 15 , 16 ] supposes that a VP is a local electrical response induced by a hydraulic wave, which propagates through a plant from the damaged zone and activates mechanosensitive Ca 2+ channels. The second hypothesis [ 4 , 17 ] supposes that the VP is the local electrical response induced by the propagation of a specific “wound substance” from the damaged zone and the activation of ligand-dependent Ca 2+ channels.…”
Section: Introductionmentioning
confidence: 99%